Runoff vs. plurality: Does it matter for expenditures? : Evidence from Italy - Davide Cipullo (Uppsala University, Department of Economics, 2018)
This paper compares the runoff system and the plurality rule in terms of the size and composition of public expenditures. I use the change in the voting rule in Italian municipalities at 15,000 residents to implement a regression discontinuity design. The results show that municipalities under the runoff system spend at least 20 percent more than those under the plurality rule, and that this effect is primarily driven by a large increase in administrative spending. Additionally, the greater number of candidates and the larger coalitions indicate lower accountability under the runoff system than under the plurality rule.
urn:nbn:se:uu:diva-363444
Keywords: D72; E02; H39; H5; 330; Voting rules; Fiscal policy; Runoff; Plurality; Regression discontinuity design